Activation of Adenosine Triphosphate–regulated Potassium Channels during Reperfusion Restores Isoflurane Postconditioning-induced Cardiac Protection in Acutely Hyperglycemic Rabbits. (June 2015) - Raphael, Jacob; Gozal, Yaacov; Navot, Nachum; Zuo, Zhiyi
Abstract : Background: Hyperglycemia is known to inhibit myocardial anesthetic postconditioning. The authors tested whether activation of adenosine triphosphate–regulated potassium (KATP ) channels would restore anesthetic postconditioning during acute hyperglycemia. Methods: Rabbits subjected to 40-min myocardial ischemia and 3-h reperfusion (ischemia–reperfusion [I/R]) were assigned to groups (n = 10 in each group) with or without isoflurane postconditioning (2.1% for 5 min) in the presence or absence of hyperglycemia and/or the KATP channel agonist diazoxide. Creatine kinase MB fraction and infarct size were measured. Phosphorylated protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS) were assessed. Oxidative stress was evaluated by measuring malondialdehyde, and apoptosis was assessed by dUTP nick-end labeling and activated caspase-3. Results: Postconditioning significantly reduced myocardial infarct size (26 ± 4% in the isoflurane [ISO] group vs. 53 ± 2% in the I/R group; P = 0.007); whereas, hyperglycemia inhibited this effect (infarct size: 47 ± 2%, P = 0.02 vs . the ISO group). Phosphorylated and eNOS levels increased, whereas malondialdehyde and myocardial apoptosis were significantly lower after isoflurane postconditioning compared with I/R. These effects were inhibited by acute hyperglycemia. Diazoxide restored the protective effect of isoflurane in the hyperglycemic animals (infarct size: 29 ± 2%; P = 0.01 vs . the I/R group), reduced malondialdehyde levels and myocardial apoptosis, but did not affect the expression of phosphorylated Akt or eNOS. Conclusions: KATP channel activation restored anesthetic postconditioning-induced myocardial protection under acute hyperglycemia. This effect occurred without increasing Akt or eNOS phosphorylation, suggesting that KATP channels are located downstream to Akt and eNOS in the pathway of isoflurane-induced myocardial postconditioning. Abstract : Adenosine triphosphate–regulated potassium channel activation restored anesthetic postconditioning-induced myocardial protection under acute hyperglycemia. This effect occurred without increasing protein kinase B (Akt) or endothelial nitric oxide synthase phosphorylation, suggesting that adenosine triphosphate–regulated potassium channels are located downstream to Akt and endothelial nitric oxide synthase in the pathway of isoflurane-induced myocardial postconditioning.